2015
DOI: 10.1038/aps.2015.90
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol protects neuroblastoma SH-SY5Y cells against Fe2+-induced apoptosis by suppressing activation of MAPK/JNK-NF-κB signaling pathway

Abstract: Aim: Carvacrol (2-methyl-5-isopropylphenol), a phenolic monoterpene in the essential oils of the genera Origanum and Thymus, has been shown to exert a variety of therapeutic effects. Here we examined whether carvacrol protected neuroblastoma SH-SY5Y cells against Fe 2+ -induced apoptosis and explored the underlying mechanisms. Methods: Neuroblastoma SH-SY5Y cells were incubated with Fe 2+ for 24 h, and the cell viability was assessed with CCK-8 assay. TUNEL assay and flow cytometric analysis were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 49 publications
(64 reference statements)
3
24
1
2
Order By: Relevance
“…When it is activated by phosphorylation, NF-κB translocates into the nucleus, where active NF-κB binds to specific DNA sequences and regulates the expression of many downstream genes, such as BCL-2. 8 In the present study, we further found that GSS inhibited the activation of NF-κB and attenuated LPS-induced NF-κB translocation from the cytoplasm into the nucleus in ECs. Our data suggested that NF-κB/BCL-2 signalling might be involved in the GSS-induced anti-apoptotic effects on LPSstimulated ECs in vitro.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…When it is activated by phosphorylation, NF-κB translocates into the nucleus, where active NF-κB binds to specific DNA sequences and regulates the expression of many downstream genes, such as BCL-2. 8 In the present study, we further found that GSS inhibited the activation of NF-κB and attenuated LPS-induced NF-κB translocation from the cytoplasm into the nucleus in ECs. Our data suggested that NF-κB/BCL-2 signalling might be involved in the GSS-induced anti-apoptotic effects on LPSstimulated ECs in vitro.…”
Section: Discussionsupporting
confidence: 74%
“…BCL-2 family proteins play an important role in cellular apoptosis process by regulating mitochondrial membrane permeability. 7 NF-κB regulates BCL-2 family proteins in immune responses, 8 and inhibition of NF-κB activity has been shown to protect against LPS-induced EC apoptosis. 9 Interestingly, our previous studies revealed that LPS-induced activation of NF-κB in ECs was mediated in a Myd88dependent manner and a Myd88-independent manner (GEF-H1 signalling pathway).…”
mentioning
confidence: 99%
“…The function of the ternary complex of IPP as a signalling platform is achieved by directly interacting with factors that function as upstream regulators of numerous different signalling pathways (21). The present study summarized the known binding partners of PINCH signaling, which are important in processes as diverse as cell adhesion, migration, proliferation, differentiation, survival and apoptosis (22,23). The results demonstrated a decrease in the pro-apoptotic proteins Bax and caspase3 and an increase in the anti-apoptotic protein Bcl-2 in the RA and UA groups compared to those of the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The experiment demonstrated that the activity of caspase‐3 was inhibited in the presence of carvacrol. These findings indicated that carvacrol might be an apoptotic inhibitor (Nafees et al , ; Cui et al , ).…”
Section: Introductionmentioning
confidence: 94%